A proposed method optimizing energy usage for software process - Candrawati, Ria; Hashim, Nor Laily; Mahmuddin, Massudi (2010)
Nowadays there are several ways that calculate the usage of carbon produce in plantations or big firms. These calculators contribute to different scopes of productions. However, the computer processes also create the amount of carbon dioxide(C02) usage. This issue can be overcome with a specific calculator that provides services to estimate the amount of carbon usage. Therefore, this paper proposes on solving the issue of carbon usage for computer processes through the use of C02 calculator.